Evaluación de riesgos laborales para conductores de SEI LTDA (2021)
The OIL & GAS sector demands continuity in the performance of tasks and requires long hours of work, characteristics that are known by all unions nationwide and directly affect workers including SEI LTDA's intervening Engineers who must to The development of their tasks requires them to travel to the exploration or production areas, in this case (Campo Ocelote) located 156 km from the urban area of Puerto Gaitán - Meta. Hazards identification, risk assessment to which engineers (Drivers) are exposed and the definition of controls were carried out to reduce the probability of occupational diseases and accidents at work.